(3eNJUQ GNJdGa GdabgGAs - (3CMeO Hf Ydj GdnqQGRj, CHh HcQ GdLUGU,J (B370 (3g` s; (3GdWMGhj , CHh LYaQ,J (B321 (3g` s
(3ChdgG (B:s
(3jHOC HHGH GdeGA GdPi NGdWJg fLGSI s
(3BNQgG (B:s
(3aCeQ cKjQ Hf GdUdJ Cf jbWY CjOjge Ke bGd YeQ aCeQ cKjQ Hf GdUdJ Efi dCQGc HLejYge hGddg dCZQ efc ZQekG jSHb Pdc de jfcQg YeQ hdG CMO ef GdUMGHI BNQ GdLRA GdChd ef eNJUQ ENJdGa GdYdeGA ddWMGhi s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B206 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B107s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B32s
Keywords: (3Gdabg GdESdGejs